2004
DOI: 10.1002/chin.200410093
|View full text |Cite
|
Sign up to set email alerts
|

The Room‐Temperature Palladium‐Catalyzed Cyanation of Aryl Bromides and Iodides with Tri‐t‐butylphosphine as Ligand.

Abstract: The Room-Temperature Palladium-Catalyzed Cyanation of Aryl Bromides and Iodides with Tri-t-butylphosphine as Ligand. -The optimized title reaction uses Zn(CN) 2 as the cyanide source and Zn-dust as a co-catalyst in DMF as the solvent. -(RAMNAUTH, J.; BHARDWAJ, N.; RENTON, P.; RAKHIT, S.; MADDAFORD*, S. P.; Synlett 2003, 14, 2237-2239; York Univ., MCR Res. Inc., Toronto, Ont. M3J 1P3, Can.; Eng.) -Mais 10-093

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Mechanistic studies revealed the main shortcoming of the reaction owing to excess dissociative of CN − to palladium (Pd) thus initiating catalyst deactivation which poisons all the intermediates in catalytic cycle. To tackle such problems, much attention was expanded to include the addition of reducing agents or applying less soluble NaCN [14,15,16,17,18,19], trimethylsilylcyanide (TMSCN) [20], KCN [21,22,23] and Zn(CN) 2 [24,25,26,27] salts in organic solvents; all these cyanide sources are universally toxic, due to the generation of hazardous hydrogen cyanide gas. Beller and colleagues introduced K 4 [Fe(CN) 6 ] as a robust and non-toxic CN − source in Pd-catalyzed coupling reactions [28] which was followed by many others using DDQ [29], N -cyano- N -phenyl- p -toluenesulfonamide [30], ethyl cyanoacetate [31], K 3 [Fe(CN) 6 ] and K 4 [Fe(CN) 6 ] [32,33,34,35,36] to name a few as safer reagents deployed in modern “cyano” chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic studies revealed the main shortcoming of the reaction owing to excess dissociative of CN − to palladium (Pd) thus initiating catalyst deactivation which poisons all the intermediates in catalytic cycle. To tackle such problems, much attention was expanded to include the addition of reducing agents or applying less soluble NaCN [14,15,16,17,18,19], trimethylsilylcyanide (TMSCN) [20], KCN [21,22,23] and Zn(CN) 2 [24,25,26,27] salts in organic solvents; all these cyanide sources are universally toxic, due to the generation of hazardous hydrogen cyanide gas. Beller and colleagues introduced K 4 [Fe(CN) 6 ] as a robust and non-toxic CN − source in Pd-catalyzed coupling reactions [28] which was followed by many others using DDQ [29], N -cyano- N -phenyl- p -toluenesulfonamide [30], ethyl cyanoacetate [31], K 3 [Fe(CN) 6 ] and K 4 [Fe(CN) 6 ] [32,33,34,35,36] to name a few as safer reagents deployed in modern “cyano” chemistry.…”
Section: Introductionmentioning
confidence: 99%